Interleukin-1β and Tumor Necrosis Factor-α Gene Polymorphisms in Systemic Sclerosis - Hakami M.A; Alotaibi B.S; Alkhalil S.S; Das S; Nasreen N; Jeraiby M.A; Jawed A; Lohani M; Dar S.A (Balkan Journal of Medical Genetics)
The complex cytokine network plays an important role in disease susceptibility and development, therefore single-nucleotide polymorphisms (SNPs) in or near cytokine genes may be relevant to development of systemic sclerosis (SSc). We in this study investigated 22 SNPs in 13 cytokine genes of SSc patients, and their association with disease susceptibility. Twenty-three clinically diagnosed SSc patients were enrolled for this purpose along with 80 healthy volunteers for comparisons. Aseptically collected 2ml of peripheral venous blood from each subject was processed for DNA extraction. Cytokine genotyping was carried out using the extracted genomic DNA by PCR employing sequence-specific primers and data was analyzed for any association with SSc susceptibility. Variations in allele, genotype, or haplotype distribution between patients and healthy volunteers were observed for the following SNPs: IL-1β –511 C/T (rs16944) and +3962 T/C (rs1143634); IL-4Rα +1902 G/A (rs1801275); IL-12 –1188 C/A (rs3212227); TGF-β1 codon 25 G/C (rs1800471); TNF-α–308 G/A (rs1800629) and –238 G/A (rs361525); IL-4 –1098 T/G (rs2243248) and –590 T/C (rs2243250); IL-6 –174 G/C (rs1800795) and nt565 G/A (rs1800797); and IL-10 –1082 G/A (rs1800896), –819 C/T (rs1800871) and –592 C/A (rs1800872). However, only the SNPs in IL-1β –511 and +3962, and TNF-α –308 and –238 were found to be significantly associated with SSc susceptibility. Our findings suggest that IL-1β and TNF-α gene SNPs may play a role in development of SSc, although large observational and experimental studies are needed to substantiate these findings.